2017
DOI: 10.4049/jimmunol.1502234
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-Presentation of Soluble and Cell-Associated Antigen by Murine Hepatocytes Is Enhanced by Collectrin Expression

Abstract: Cross-presentation is a modular series of intracellular events dictating the internalization and subsequent MHC class I (MHC I) display of extracellular Ags. This process has been defined in dendritic cells and plays a fundamental role in the induction of CD8 T cell immunity during viral, intracellular bacterial, and antitumor responses. Herein, acute viral infection of murine liver with adenovirus, a model for intrahepatic cross-presentation, confirms hepatocytes directly contribute to cross-presentation of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Liver sinusoidal endothelial cells, Kupffer cells, and hepatocytes also contribute to cross-presentation and expansion of CD8 T cells within the mouse liver during acute adenoviral infection (36). Hepatocyte expression of collectrin, a membrane protein found to promote vesicle fusion during insulin exocytosis by pancreatic β cells (37), has curiously been linked to the expansion of virus-specific CD8 T cells and viral clearance after adenovirus infection (38). Collectrin augmented hepatocyte and not hematopoietic cell cross-presentation and cross-priming of antigen-specific CD8 T cells in vitro in response to either soluble antigen or remnants of infected necrotic hepatocytes (38).…”
Section: The Cells That Conduct Cross-presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver sinusoidal endothelial cells, Kupffer cells, and hepatocytes also contribute to cross-presentation and expansion of CD8 T cells within the mouse liver during acute adenoviral infection (36). Hepatocyte expression of collectrin, a membrane protein found to promote vesicle fusion during insulin exocytosis by pancreatic β cells (37), has curiously been linked to the expansion of virus-specific CD8 T cells and viral clearance after adenovirus infection (38). Collectrin augmented hepatocyte and not hematopoietic cell cross-presentation and cross-priming of antigen-specific CD8 T cells in vitro in response to either soluble antigen or remnants of infected necrotic hepatocytes (38).…”
Section: The Cells That Conduct Cross-presentationmentioning
confidence: 99%
“…Hepatocyte expression of collectrin, a membrane protein found to promote vesicle fusion during insulin exocytosis by pancreatic β cells (37), has curiously been linked to the expansion of virus-specific CD8 T cells and viral clearance after adenovirus infection (38). Collectrin augmented hepatocyte and not hematopoietic cell cross-presentation and cross-priming of antigen-specific CD8 T cells in vitro in response to either soluble antigen or remnants of infected necrotic hepatocytes (38). Its role in cross-presentation in these cell types may be related to facilitating vesicular fusion events important for cross-presentation (37, 39).…”
Section: The Cells That Conduct Cross-presentationmentioning
confidence: 99%
“…Indeed, hepatocytes are capable of priming naïve CD8 + T-cells directly and via cross-presentation ( 20 , 45 ) but fail to provide the activated CD8 + T-cells with the necessary survival factor and therefore cause CD8 + T-cell deletion ( 45 , 46 ). A recent study showed that the pathway of antigen processing and loading of MHC-I complex depends on a specific chaperone in the endoplasmatic reticulum–Golgi intermediate compartment called collectrin ( 47 ). This protein is not expressed in KCs or DCs and indicates a distinct mechanism of antigen processing for cross-presentation in hepatocytes ( 47 ).…”
Section: Presentation Of Antigens On Major Histocompatibility Complexmentioning
confidence: 99%
“…A recent study showed that the pathway of antigen processing and loading of MHC-I complex depends on a specific chaperone in the endoplasmatic reticulum–Golgi intermediate compartment called collectrin ( 47 ). This protein is not expressed in KCs or DCs and indicates a distinct mechanism of antigen processing for cross-presentation in hepatocytes ( 47 ).…”
Section: Presentation Of Antigens On Major Histocompatibility Complexmentioning
confidence: 99%
“…Paul-Heng et al have found that direct recognition of hepatocyte expressed MHC-I alloantigen (cross presentation) is required for tolerance induction, whereas the indirect recognition of the processed and presented allogeneic peptide on MHC-II by CD4 T cells is not sufficient for tolerance induction although it can prolong the graft survival and generate Tregs to promote transplant tolerance (78, 79). Additionally, processing of the soluble antigens into peptide presented by MHC-I is impaired in hepatocytes lacking collectrin, which is an intracellular chaperone protein within the endoplasmic reticulum-Golgi intermediate compartment and positively regulated (80). Different from other liver cells, hepatocytes can produce exosomes to control the active T cells response and clear the activated T cells through the non-apoptotic way of suicidal emperipolesis (SE), which is a process leading to cell-in-cell structures and promotes cell death through degradation within endosomal/lysosomal compartments (Figure 3) (81, 82).…”
Section: Interactions Of Hepatocytes and Alloreactive T Cellsmentioning
confidence: 99%